The Sufficiency Exam in the perception of accounting students - Silva, Joelson Viscovini da (2020)
The Sufficiency Exam is defined by the Federal Accounting Council (CFC) as an equalization test, designed to prove the achievement of average knowledge, according to the syllabus developed in the Bachelor of Science courses in Accounting. Considering this context, this article aims to identify students' perceptions about taking the sufficiency test. The study is classified as an exploratory-descriptive research, with data collection performed by means of a questionnaire applied by the researchers in person, with the participation of 188 undergraduate students in Accounting Sciences (about 58.75% of the population), from a public university of the State of Mato Grosso, in 2019. Data have been treated with the following statistical techniques: descriptive statistics (mean, median, frequency, maximum, minimum and sum) and factor analysis. The research results indicate that the importance and need to apply the sufficiency test for the accounting profession is considered most valued by the students. In the factor analysis, it became evident that professional valorization has a greater weight in the students' perceptions (88.15%), followed by the academic environment with 6.39%. We come to the conclusion that the Sufficiency Exam, at a students' perception, is an instrument that values the accounting profession, however it is necessary that teachers discuss this theme more punctually in classroom.